Physicochemical, thermal properties, and in vitro rumen fermentation of four different underutilized fruit by-products - RUSLI FIDRIYANTO; GUNAWAN PRIADI; RONI RIDWAN; NAHROWI NAHROWI; ANURAGA JAYANEGARA (Society for Indonesian Biodiversity, 2023)
Abstract. Fidriyanto R, Priadi G, Ridwan R, Nahrowi N, Jayanegara A. 2023. Physicochemical, thermal properties, and in vitro rumen fermentation of four different underutilized fruit by-products. Biodiversitas 24: 2416-2425. The objective of this study was to investigate the potential use of selected agricultural wastes consisting of Mangosteen (Garcinia mangostana L.) Peel (MGP), pomegranate (Punica granatum L.) Peel (PGP), kaffir lime (Citrus hystrix DC.) Peel (KLP), and Melastoma candidum D.Don Fruit (MCF) as ruminant feeds and enteric methane mitigation. The samples were analyzed for proximate, phytochemical, enzyme inhibition activity, XRD, FTIR, TGA, and in vitro rumen fermentation. The study found that MCF had the highest protein content (105.69 g/kg DM), while KLP had the lowest crude fiber (115.89 g/kg DM). MCF extract had the highest total phenol and flavonoid, and PGP extract had the highest enzyme inhibition activity. XRD analysis showed that KLP had the highest crystallinity (18.23%), followed by MCF (17.95%). KLP had the highest potential gas production (147.78 mL), followed by PGP (62.20 mL), MCF (27.86 mL), and MGP (4.46 mL). In addition, rumen digestibility, post-rumen digestibility, and VFA followed a similar pattern. The lowest methane production was observed in MGP and MCF. In conclusion, kaffir lime peel is potentially used as ruminant feed due to its higher digestibility and VFA production. Although MCF has lower digestibility, it is potentially used as a source of phenolic compounds to reduce methane production due to its higher phenolic and flavonoid content.